Housing and personality effects on judgement and attention biases in dairy cows - Louise Kremer (Nature Portfolio, 2021)
Abstract Affective states can be inferred from responses to ambiguous and threatening stimuli, using Judgement Bias Tasks (JBTs) and Attention Bias Tasks (ABTs). We investigated the separate and interactive effects of personality and housing conditions on dairy cattle affective states. We assessed personality in 48 heifers using Open-Field, Novel-Object and Runway tests. Personality effects on responses to the JBT and to the ABT were examined when heifers were housed under reference conditions. Heifers were subsequently housed under positive or negative conditions, and housing effects on animal responses in both tasks were investigated while controlling for personality. A Principal Component Analysis revealed three personality traits labelled Activity, Fearfulness and Sociability. Under reference conditions, personality influenced heifers’ responses to the JBT and to the ABT, therefore questioning the tasks’ generalizability across individuals. Against expectations, housing did not influence responses to the  JBT and heifers in the negative conditions looked at the threat later than heifers in the positive or reference conditions. More research is warranted to confirm the validity and the repeatability of the JBT and of the ABT as appropriate measures of affective states in dairy cows.